36.6k views
1 vote
Find the antiderivative for the function f(x) = (x – 11)(x + 13).

Please help

User Ajadex
by
5.6k points

2 Answers

3 votes

Expanding the product is simple enough:


(x-11)(x+13)=x^2+2x-143

Then


\displaystyle\int(x-11)(x+13)\,\mathrm dx=\frac{x^3}3+x^2-143x+C

We could also use a subsitution like
u=x-11, so that
u+24=x+13 and
\mathrm du=\mathrm dx:


\displaystyle\int u(u+24)\,\mathrm du=\int(u^2+24u)\,\mathrm du=\frac{u^3}3+12u^2+C


\implies\displaystye\int(x-11)(x+13)\,\mathrm dx=\frac{(x-11)^3}3+12(x-11)^2+C

(which is differs from the first result by a constant, so it's still valid)

User Alex Soroka
by
5.4k points
6 votes

Answer:

1/3x^3+x^2-143x+c

Explanation:

i got it right on the test

User David Kolar
by
6.1k points